Peran Sistem Informasi Manajemen dalam Kepemimpinan Pendidikan Islam - Fikri Maulyda; Sri Mulyani (CV. ITTC INDONESIA, 2026)
The rapid advancement of information technology has transformed governance across various sectors, including Islamic educational institutions. Educational Management Information Systems (EMIS) have become strategic instruments for improving the effectiveness of school and madrasah management, particularly in planning, organizing, supervising, and decision-making processes. This article aims to analyze the concept of Educational Management Information Systems, their implementation in schools and madrasahs, their role in Islamic educational leadership, as well as the challenges and strategies for successful implementation. This study employed a qualitative approach using a library research method. Data were collected from scientific books, journal articles, government regulations, and other official documents related to Educational Management Information Systems. Data were analyzed using content analysis techniques. The findings indicate that Educational Management Information Systems significantly enhance the effectiveness of school leadership by providing accurate, timely, and integrated information. Various digital platforms such as Dapodik, EMIS, ARKAS, e-RKAM, and e-Rapor contribute to more transparent, accountable, and efficient educational governance. Nevertheless, several challenges remain, including limited digital literacy, inadequate technological infrastructure, data security issues, and resistance to organizational change. Therefore, strengthening human resource competencies and institutional support is essential to optimize the implementation of management information systems and improve the quality of Islamic education sustainably.